2021
DOI: 10.1186/s10020-021-00333-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally specific roles of TLR4, TNF, and IL-17A in murine endotoxin-induced inflammation inferred from analysis of dynamic networks

Abstract: Background Bacterial lipopolysaccharide (LPS) induces a multi-organ, Toll-like receptor 4 (TLR4)-dependent acute inflammatory response. Methods Using network analysis, we defined the spatiotemporal dynamics of 20, LPS-induced, protein-level inflammatory mediators over 0–48 h in the heart, gut, lung, liver, spleen, kidney, and systemic circulation, in both C57BL/6 (wild-type) and TLR4-null mice. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…We have reported previously that the expression of TLR4 impacts dynamic networks of inflammation induced by LPS in mice ( 14 , 15 ). We therefore hypothesized that the expression of TLR4 impacts the cross-compartment spread of inflammation, and thus compared the dynamic evolution of inflammation in WT and TLR4 -/- mice following T/HS-R.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have reported previously that the expression of TLR4 impacts dynamic networks of inflammation induced by LPS in mice ( 14 , 15 ). We therefore hypothesized that the expression of TLR4 impacts the cross-compartment spread of inflammation, and thus compared the dynamic evolution of inflammation in WT and TLR4 -/- mice following T/HS-R.…”
Section: Resultsmentioning
confidence: 99%
“…A key, unanswered question remains that of how trauma/hemorrhage impact immuno-inflammatory responses in various organs and the systemic circulation. We have recently begun to address this question in the simpler context of experimental endotoxemia in mice, utilizing computational methods aimed at defining the temporal hierarchy of the cross-tissue progression of inflammation, dynamic networks of inflammation, and the hallmarks of pathological systemic spillover of inflammation ( 14 , 15 ). These studies also implicated type 17 immune responses in the spatiotemporal elaboration of inflammation ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Dalby et al ( 74 ) showed that deletion of the TLR4 and co-receptor CD14, which are involved in LPS signaling ( 60 , 61 ), did not prevent diet-induced obesity in mice, suggesting that obesity may develop independent of LPS and metabolic endotoxemia. Intriguingly, intestinal permeability and LPS levels were raised in obese TLR4 and CD14 knockout mice ( 74 ), suggesting that LPS could signal through an unidentified TLR4-independent pathway ( 75 ). Importantly, knockout of TLR4 in specific cell populations such as intestinal epithelial cells (IECs) rather than whole-body knockout may be required to induce metabolic effects ( 66 ).…”
Section: The Intestinal Immunological Barrier In Obesity and T2dmentioning
confidence: 99%